(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
According to the study, education consists in changing natural growth. It should consider reconcile the inborn existence of a human being in the ways of society. Education involves improving the child’s behavior. The instructor must adjust the student’s actions toward current social circumstances. In other words, behavioral adjustment in the direction of social ideals or circumstances should take place. Education is a development process, and it will make a person self-reliant, mentally mature, socially successful, culturally refinable, morally virtuous and spiritually advanced. In the field of teacher education, computer education is already a compulsory subject, with teachers and students beginning to apply PCS training in all areas of teacher education. During PCS preparation, teachers were found to be receptive to the integration of PCS education in the meaning of facilities, knowledge, skills, applications and assessment. The investigator took the present research problem on the expectations of teacher educators in the application of computer in the teaching learning process following a number of previous investigations research articles in journals, and several research papers published on this topic.